KONTAMINASI ESCHERICHIA COLI PADA MAKANAN JAJANAN DI KANTIN SEKOLAH DASAR NEGERI WILAYAH DENPASAR SELATAN - Nuryani, Dewi; Adiputra, Nyoman; Sudana, Ida Bagus (ECOTROPHIC : Jurnal Ilmu Lingkungan (Journal of Environmental Science); Vol 10 No 1 (2016)DO - 10.24843/EJES.2016.v10.i01.p05, 2016)
Snacks at the Public Elementary School Canteen has a huge potential in the nutrition of schoolchildren, as it also has a level of vulnerability that can cause diarrhea if not to be improved maximally .The purpose of this study was to determine the factors associated with the incidence of E. coli contamination in snacks in the canteen of the Public Elementary School at area of South Denpasar District. The research was conducted with cross-sectional design on 31 canteen of Public Elementary Schools in at area of South Denpasar District in January to March 2015 .The statistical test used was chi-square method. Positive E. coli contamination in food snacks of the Publick Elementary School Canteen at area of South Denpasar District were occur in amount of 71 % and 29 % negative. The factors related to the E. coli contamination in the snacks were foodstuffs ( p = 0.037 ) , storage of foodstuffs ( p = 0.041 ) , food- processing ( p = 0.037 ) , sanitary facilities ( p = 0.015 ) and power handlers ( p = 0.037 ) . The most dominant factors related to E. coli contamination in snacks of the canteens of Public Elementary School at area of South Denpasar District is sanitation facilities especially the water which have been used in process of the food-snack preparation .Suggested to all state elementary school cafeteria Region South Denpasar to improve environmental sanitation and water sources are more hygienic.
Keywords: E.coli contamination , snack, diarrhea, elementary school canteen